SMART FINANCIAL MANAGEMENT IN ISLAMIC BOARDING SCHOOLS: EVALUATING THE E-BEKAL APPLICATION FOR TRANSPARENT AND ACCOUNTABLE GOVERNANCE - Abim Valerina; Romzatul Widad (JURNAL PROFIT, 2026)
This study examines the implementation of the E-Bekal application in the financial management system of Pondok Pesantren Nurul Jadid, with a focus on improving transparency, accountability, and efficiency in managing students’ funds. The study emerged from the need to modernize pesantren financial governance in response to administrative complexity and the growing demand for more transparent institutional management. Before the implementation of E-Bekal, financial transactions were handled manually through the Simpan Santri (SS) and Simpan Bekal Santri (SBS) systems. These conventional mechanisms often caused problems such as recording inaccuracies, delayed reporting, limited access to financial information, and weak internal control over cash flow and fund usage. This research uses a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation. The findings show that E-Bekal has transformed financial management from a fragmented manual system into an integrated digital system. The application records transactions automatically and in real time, reducing the risk of human error, strengthening monitoring mechanisms, and preventing misuse of funds. It also enables parents to monitor their children’s financial activities directly, thereby increasing trust and participatory oversight. For pesantren administrators, E-Bekal facilitates the preparation of financial reports that are more accurate, systematic, and timely, while also improving administrative efficiency. In conclusion, the implementation of E-Bekal represents a significant step in the digital transformation of pesantren financial governance. The application not only enhances transparency and accountability but also increases operational efficiency. This study suggests that digital financial applications such as E-Bekal can serve as a strategic model for other Islamic boarding schools seeking to modernize their governance systems in the era of financial technology.